PEMBERDAYAAN PEMUDA KARANG TARUNA MELALUI PROGRAM BUSINESS CREATIVE - Achmad Saiful Ulum; Chitra Laksmi Rithmaya (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2022)
The Youth Organization is a forum that can be used for coaching, developing, and empowering youth communities in an effort to create new jobs or increase the potential of products that have been produced. In this KKN, it will be carried out on Youth Karang Taruna who are in RW VIII, Gunung Anyar Village, Surabaya. Kartar, Gunung Anyar Village, Surabaya plays an active role in development and improvement through culinary businesses or in collaboration with the home industry, but is constrained by the interest of Kartar youth who still have fun in youth activities and activities more than just get-togethers. , hang out, play online games and eat. - eat, so there is still a lack of productivity in Kartar in the village. The method in KKN which was carried out on Karang Taruna Youth in RW VIII, Gunung Anyar Village, Surabaya, was the method of Material Exposure, Practicum, and Mentoring. The results of this KKN include: Increased basic knowledge about the essence of Entrepreneurship, Youth Able to Create and Develop Business Ideas that are ready to be Implemented, able to determine and assess Market Opportunities through Business Feasibility Study Analysis and being able to produce Creative Businesses that can be proven from processed products produced and packaged ready to be marketed and have global competitiveness.Kata kunci: Youth Organization, Creative Business, Market Opportunity and Global